Dynamically tunable multi-lobe laser generation via multifocal curved beam - Xing, Enbo (2019)
Beams with curved properties, represented by Airy beam, have already shown potential applications in various fields. Here we propose a simple method to achieve a multifocal curved beam (MCB). The scheme is based on the ability of microspheres to control the distribution of the light field. Combined with the caustic effect, the dynamic control of the beam curvature and the foci can be realized. The simulation results confirm the mechanism behind this phenomenon. Furthermore, MCB is applied experimentally into the end-pumped microchip laser. This work has verified the theory of MCB and achieved a dynamically tunable multi-lobe laser, which has a wide application prospect.